PERANAN NUMBER HEADS TOGETHER DALAM PEMBELAJARAN BIOLOGI DI KELAS XI IPA - Rahmaniati, Ernita (Universitas Tanjungpura, 2015)
This research motivated presence of symptoms that can be seen in the field that the biological activity and learning outcomes have not achieved the expected result of 78. The cause of the low biological activity and learning outcomes is presumably because the teacher actively describes the material, give examples, and exercises while students just listen, take notes, and do the exercises. Learning as it failed to give students the chance to discover, establish and develop his own knowledge. This type of research is done in an attempt repair of the problems mentioned above is a Classroom Action Research. Data of this research is taken using an instrument tests, observation sheet and evaluation test results are processed in a qualitative study. The results showed that by using cooperative learning type Number Heads Together can increase the activity of learning and learning outcomes of students of class XI IPA1 SMA 4 Pontianak. Keywords : Activity, learning outcomes, Number Heads Together.